Heavy-rare-earth-free high-residual-magnetism high-coercive-force magnet and preparation method thereof
By adjusting the content of elements such as B, Cu, Co, Al in the neodymium iron boron magnet, and using the third-level aging and secondary sintering process, the microstructure structure of the magnet is optimized, and the problem of improving the magnet residual magnet, coercivity and square consistency without adding heavy rare earths is solved, and higher magnet performance is achieved.
Patent Information
- Application Number
- CN202411973149.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-30
AI Technical Summary
How to improve the consistency of residual magnetism, coercivity and squareness of neodymium iron boron sintered magnet without adding or less heavy rare earths?
By reasonably controlling the content of elements such as B, Cu, Co, Al in the raw material components, and combining the third-level aging process and the second-level sintering process, the microstructure structure of the magnet is optimized, the proportion of R6T13M1 phase is increased, the redistribution of elements such as Cu, Co, etc. is promoted, and the fine regulation of the magnet grain boundary structure is achieved.
Without adding heavy rare earths, the coercive force and residual magnetism of the magnet are effectively improved, the consistency of squareness is improved, and the overall performance of the magnet is improved.
Smart Images

Figure CN119763966A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of magnetic materials, and more specifically, to a heavy rare earth-free high remanence and high coercivity magnet and a preparation method thereof. Background Art
[0002] Since its introduction, rare earth magnetic materials have been widely used in energy, transportation, machinery, medical appliances and other industries due to their excellent magnetic properties, and their products also involve many areas of the national economy. At present, the development of electric vehicles, wind power generation and other fields has been rapid, and the demand for improving the performance of permanent magnets is also gradually increasing.
[0003] Since many applications of NdFeB sintered magnets are in high temperature environments, they are required to have not only high remanence but also high coercivity. Among them, coercivity is the main parameter of permanent magnet materials. The higher the coercivity, the stronger its anti-demagnetization ability. In application, the higher the coercivity of NdFeB sintered magnets, the better, and it can ensure that it has good temperature stability and can work under higher temperature conditions. The common method to improve the coercivity of NdFeB sintered magnets is to use Dy and Tb instead of Nd to improve the coercivity. However, the reserves of heavy rare earths Dy and Tb are scarce, the price is expensive, and the remanence of the magnet will be reduced. In addition, heavy rare earths such as Dy and Tb are susceptible to the impact of rare earth policies, which brings the risk of unstable or large fluctuations in prices. Therefore, how to obtain rare earth permanent magnets with good consistency in remanence, coercivity and squareness without adding or adding less heavy rare earths is an urgent problem to be solved in this field. Summary of the invention
[0004] In order to at least solve one or more of the technical problems mentioned above, the present application proposes solutions for improving the prior art in multiple aspects.
[0005] According to a first aspect of the present application, the present application provides a neodymium iron boron magnet, the neodymium iron boron magnet comprising main phase grains, a thin layer grain boundary phase and a triangular region grain boundary phase, the neodymium iron boron magnet comprising:
[0006] R: 28~33wt%
[0007] B: 0.84~0.94wt%,
[0008] Co: 0.05~1wt%,
[0009] Cu: 0.05~0.55wt%,
[0010] Ga: 0.3~0.6wt%,
[0011] M2: 0-0.55wt%, wherein M2 is selected from one or both of Al and Sn,
[0012] M3: 0.1-0.6wt%, wherein M3 is selected from one or two of Zr and Ti,
[0013] Fe: 66-70wt%;
[0014] Wherein, R is a rare earth element, and R includes at least PrNd;
[0015] The triangular region grain boundary phase includes R6T 13 M1 phase, the R6T 13 The M1 phase includes M elements and T elements, wherein the M elements are selected from any two or more elements of Al, Cu, Ga, Ti, Sn and / or Zr, and the T elements include Fe and / or Co; all R6T 13 The percentage of the sum of the areas of the M1 phase to the total area of the microstructure cross section is 5.20% to 8.40%.
[0016] According to one embodiment of the present application, the NdFeB magnet is composed of the following components:
[0017] R: 28~31wt%
[0018] B: 0.84~0.92wt%
[0019] Co: 0.05-0.6wt%,
[0020] Cu: 0.3~0.55wt%,
[0021] Al: 0~0.35wt%,
[0022] Ga: 0.3~0.48wt%,
[0023] M3: 0.15~0.3wt%
[0024] Fe: 66~70wt%.
[0025] According to one embodiment of the present application, the distribution of the triangular region grain boundary phase satisfies the following conditions: the area of all triangular region grain boundary phases in the cross section of the NdFeB magnet microstructure accounts for 6.5% to 8.5% of the total area of the cross section; and the triangular region grain boundary phase includes R6T 13 M1 phase and R-rich phase, the R6T 13 The distribution of the M1 phase satisfies the following conditions: all R6T 13 The percentage of the area of the M1 phase to the total area of the cross section is 5.90% to 8.4%.
[0026] According to one embodiment of the present application, the R6T 13The M1 phase includes Cu element, and the R6T 13 The average atomic percentage of Cu element in the M1 phase is 1.5% to 7%.
[0027] According to one embodiment of the present application, the R-rich phase includes Cu element, and the average atomic percentage of Cu element in the R-rich phase is 3.50% to 11.00%, preferably 3.50% to 7.60%.
[0028] According to one embodiment of the present application, the R6T 13 The M1 phase includes Co element, and the R6T 13 The average atomic percentage of Co element in the M1 phase is 0.50% to 4%.
[0029] According to one embodiment of the present application, the R-rich phase includes Ga element, and the average atomic percentage of Ga element in the R-rich phase is 0.3-1.5%.
[0030] According to one embodiment of the present application, the NdFeB magnet comprises:
[0031] R: 29.5~32wt%
[0032] B: 0.84~0.92wt%
[0033] Al: 0.3~0.55wt%,
[0034] Ga: 0.3~0.48wt%,
[0035] Co: 0.05-0.6wt%,
[0036] Cu: 0.05-0.3wt%,
[0037] Fe: 66~70wt%.
[0038] According to one embodiment of the present application, the R6T 13 The distribution of the M1 phase satisfies the following conditions: all R6T 13 The percentage of the area of the M1 phase to the total area of the cross section is 5.3% to 7.9%.
[0039] According to one embodiment of the present application, the R6T 13 The M1 phase contains Ga, and [Ga] represents the R6T 13 Ga atomic percentage in the M1 phase, [M] represents the R6T 13 The atomic percentage of M element in the M1 phase is [Ga] / [M]=0.49~0.61.
[0040] According to one embodiment of the present application, the R6T 13 The M1 phase contains Al, and [Al] represents the R6T 13 The atomic percentage of Al in the M1 phase, [M] represents the R6T 13 The atomic percentage of M element in the M1 phase is [Al] / [M]=0.32~0.45.
[0041] According to one embodiment of the present application, R does not include heavy rare earth elements.
[0042] According to a second aspect of the present application, the present application provides a method for preparing a neodymium iron boron magnet, which comprises:
[0043] 1) using a predetermined raw material alloy to form a quick-setting alloy sheet by a quick-setting process;
[0044] 2) The quick-setting alloy flakes obtained in step 1) are subjected to hydrogen explosion pulverization and jet mill pulverization to obtain alloy powder, wherein the average particle size D50 of the alloy powder is 3 to 5 μm;
[0045] 3) pressing the alloy powder obtained in step 2) under magnetic field orientation, the magnetic field strength is 1.4-2.5T, to obtain a compact, or the alloy powder is pressed under magnetic field orientation and then isostatically pressed to obtain a compact;
[0046] 4) placing the compact obtained in step 3) into a sintering furnace, and performing sintering and aging treatment in a vacuum or inert atmosphere to finally obtain a NdFeB magnet;
[0047] The aging treatment process is a three-level aging process: the temperature of the first level aging is 800-950°C, and the insulation time is 0.5-4h; the temperature of the second level aging is 450-550°C, and the insulation time is 2-10h; the temperature of the third level aging is 600-700°C, and the insulation time is 2-10h.
[0048] According to one embodiment of the present application, in the step 4), the aging treatment process further includes: cooling to 150-250°C after the second stage aging, with a cooling rate of 3-8°C / min; cooling to room temperature after the third stage aging, with a cooling rate of 3-8°C / min.
[0049] The present invention effectively optimizes the microstructure of the magnet by reasonably controlling the content of B, Cu, Co, Al and other elements in the raw material composition and combining the process of secondary sintering and / or tertiary aging. In particular, the tertiary aging heat treatment can further promote the intergranular reaction, which not only improves the R6T 13 The proportion of M1 phase also promotes the redistribution of elements such as Cu and Co, thereby effectively improving the coercive force of the magnet without adding or adding less heavy rare earth elements. BRIEF DESCRIPTION OF THE DRAWINGS
[0050] By reading the detailed description below with reference to the accompanying drawings, the above and other purposes, features and advantages of the exemplary embodiments of the present application will become easy to understand. In the accompanying drawings, several embodiments of the present application are shown in an exemplary and non-limiting manner, and the same or corresponding reference numerals represent the same or corresponding parts, wherein:
[0051] Figure 1 A scanning electron microscope photograph of a microstructure cross section of the magnet of Example 1-1 of the present application is shown;
[0052] Figure 2 A scanning electron microscope photograph of a microstructure cross section of the magnet of Comparative Example 1-1 of the present application is shown;
[0053] Figure 3 A scanning electron microscope photograph of a microstructure cross section of the magnet of Example 2-1 of the present application is shown;
[0054] Figure 4 A scanning electron microscope photograph of a microstructure cross section of the magnet of Comparative Example 2-1 of the present application is shown. DETAILED DESCRIPTION
[0055] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present application.
[0056] It should be understood that the terms "include" and "comprising" used in the specification and claims of the present application indicate the presence of described features, wholes, steps, operations, elements and / or components, but do not exclude the presence or addition of one or more other features, wholes, steps, operations, elements, components and / or collections thereof.
[0057] It should also be understood that the terms used in this application specification are only for the purpose of describing specific embodiments and are not intended to limit the present application. As used in this application specification and claims, unless the context clearly indicates otherwise, the singular forms of "a", "an" and "the" are intended to include plural forms. It should also be further understood that the term "and / or" used in this application specification and claims refers to any combination of one or more of the associated listed items and all possible combinations, and includes these combinations.
[0058] The specific implementation methods of the present application are described in detail below in conjunction with the accompanying drawings. Unless otherwise specified, the materials, reagents and equipment used in the examples of the present application are all obtained from conventional commercial channels.
[0059] According to a first aspect of the present application, the present application provides a neodymium iron boron magnet, the neodymium iron boron magnet comprising main phase grains, a thin layer grain boundary phase and a triangular region grain boundary phase, wherein the neodymium iron boron magnet comprises:
[0060] R: 28~33wt%
[0061] B: 0.84~0.94wt%,
[0062] Co: 0.05~1wt%,
[0063] Cu: 0.05~0.55wt%,
[0064] Ga: 0.3~0.6wt%,
[0065] M2: 0-0.55wt%, wherein M2 is selected from one or both of Al and Sn,
[0066] M3: 0.1-0.6wt%, wherein M3 is selected from one or two of Zr and Ti,
[0067] Fe: 66~70wt%
[0068] Wherein, R is a rare earth element, and R includes at least PrNd;
[0069] The triangular region grain boundary phase includes R6T 13 M1 phase, the R6T 13 The M1 phase includes M elements and T elements, wherein the M elements are selected from any two or more elements of Al, Cu, Ga, Ti, Sn and / or Zr, and the T elements include Fe and / or Co. The R6T 13 The percentage of the sum of the areas of the M1 phase to the cross-sectional area of the microstructure is 5.2% to 8.4%.
[0070] In order to reduce the use of heavy rare earths, when the present application adopts a formula system with lower B content and higher Ga content, the magnet with lower B content is more sensitive to temperature. During mass production, slight changes in B content may cause problems with the consistency of the magnet. Usually, the instability in the preparation method can be eliminated by adding a certain amount of high-melting point metals (Ti, Zr, Nb, etc.) to form compounds such as ZrB2 and TiB2 at the grain boundaries of the triangular region, but the addition of high-melting point elements may reduce the remanence of the magnet. The present application effectively optimizes the microstructure of the magnet by reasonably adjusting the content of elements such as B, Cu, Co, Al in the raw material components, and combining specific sintering and aging processes. In particular, when only a small amount of high-melting point metal is added, combined with specific sintering and aging treatment processes, the R6T 13 The proportion of M1 phase promotes R6T 13 The uniform distribution of Cu, Ga and Co elements in the M1 phase effectively improves the remanence and coercive force of the magnet.
[0071] NdFeB magnets include main phase grains, thin layer grain boundary phases and triangular region grain boundary phases. The thin layer grain boundary phase refers to the grain boundary phase formed between two adjacent main phase grains, while the triangular region grain boundary phase refers to the grain boundary phase surrounded by three or more main phase grains.
[0072] In some embodiments, R does not include heavy rare earth elements. Without adding heavy rare earth elements, the present application effectively improves the remanence and coercivity of the magnet.
[0073] In some embodiments, the NdFeB magnet comprises:
[0074] R: 28~31wt%
[0075] B: 0.84~0.92wt%
[0076] Co: 0.05-0.6wt%,
[0077] Cu: 0.3~0.55wt%,
[0078] Al: 0~0.35wt%,
[0079] Ga: 0.3~0.48wt%,
[0080] M3: 0.15~0.3wt%
[0081] Fe: 66~70wt%.
[0082] In order to reduce the usage of heavy rare earth, it is necessary to adopt a formula system with lower B content and higher Ga content. In particular, for the preparation of magnets with lower rare earth content and higher remanence, when the Cu content is higher and the Al content is lower in the magnet composition, the inventors have found through research that the triangular grain boundary region of the magnet is prone to form a Cu-rich R-rich phase. The presence of this R-rich phase is not conducive to the formation of R6T with uniform distribution of rare earth elements and elements such as Cu and Co. 13 The M1 phase limits the increase in the coercivity of the magnet. 13 The amount and uniform distribution of M1 phase have a great influence on the coercive force of the magnet.
[0083] The present invention effectively optimizes the microstructure of the magnet by rationally controlling the contents of B, Cu, Co, Al, and Ga in the raw material components and combining the three-stage aging process. In particular, after the three-stage aging heat treatment, the R-rich grain boundary phase with a high Cu content in the magnet further undergoes intergranular reaction and is converted into R6T 13 M1 phase. In this way, R6T 13 The proportion of M1 phase also promotes the redistribution of elements such as Cu and Co, which reduces the content of Cu and / or Ga in the R-rich phase. 13 The element content of Cu and / or Co in the M1 phase is increased, so that the grain boundary structure of the magnet can be finely controlled, thereby effectively improving the coercive force of the magnet.
[0084] In some embodiments, the composition of the NdFeB magnet includes R: 28-31 wt%. For example, the content of R can be 28.0 wt%, 28.2 wt%, 28.5 wt%, 28.8 wt%, 29.0 wt%, 29.2 wt%, 29.5 wt%, 29.8 wt%, 30.0 wt%, 30.2 wt%, 30.5 wt%, 30.8 wt%, 31.0 wt% or any value within the range of any of the above values.
[0085] In some embodiments, the composition of the NdFeB magnet includes 0.84-0.92 wt % of B. For example, the content of B can be 0.84 wt %, 0.85 wt %, 0.86 wt %, 0.87 wt %, 0.88 wt %, 0.89 wt %, 0.90 wt %, 0.91 wt %, 0.92 wt % or any value within the range of any of the above values.
[0086] In some embodiments, the composition of the NdFeB magnet includes Co: 0.05-0.6 wt %. For example, the content of Co can be 0.05%, 0.10 wt %, 0.15 wt %, 0.20 wt %, 0.25 wt %, 0.30 wt %, 0.35 wt %, 0.40 wt %, 0.45 wt %, 0.50 wt %, 0.55 wt %, 0.60 wt % or any value within the range of any of the above values.
[0087] In some embodiments, the composition of the NdFeB magnet includes Cu: 0.3-0.55 wt%. For example, the content of Cu can be 0.30 wt%, 0.32 wt%, 0.35 wt%, 0.38 wt%, 0.40 wt%, 0.42 wt%, 0.45 wt%, 0.48 wt%, 0.50 wt%, 0.52 wt%, 0.55 wt% or any value within the range of any of the above values.
[0088] In some embodiments, the composition of the NdFeB magnet includes Al: 0-0.35 wt %. For example, the content of Al can be 0.05 wt %, 0.10 wt %, 0.15 wt %, 0.20 wt %, 0.25 wt %, 0.30 wt %, 0.35 wt % or any value within the range of any of the above values.
[0089] In some embodiments, the composition of the NdFeB magnet includes Ga: 0.3-0.48 wt %. For example, the content of Ga can be 0.30 wt %, 0.32 wt %, 0.35 wt %, 0.38 wt %, 0.40 wt %, 0.42 wt %, 0.45 wt %, 0.48 wt % or any value within the range of any of the above values.
[0090] In some embodiments, the composition of the NdFeB magnet includes M3: 0.15-0.3 wt %. For example, the content of M3 can be 0.15 wt %, 0.16 wt %, 0.18 wt %, 0.20 wt %, 0.22 wt %, 0.24 wt %, 0.26 wt %, 0.28 wt %, 0.30 wt % or any value within the range of any of the above values.
[0091] In some embodiments, the distribution of the triangular region grain boundary phase satisfies the following conditions: the percentage of the area of all triangular region grain boundary phases in the microstructure cross section of the NdFeB magnet to the total cross section area is 6.5% to 8.5%; and the triangular region grain boundary phase includes R6T 13M1 phase and R-rich phase. Exemplarily, the percentage of the area of all triangular grain boundary phases in the microstructural cross section of the NdFeB magnet to the total area of the cross section can be 6.5%, 6.6%, 6.7%, 6.8%, 6.9%, 7.0%, 7.1%, 7.2%, 7.3%, 7.4%, 7.5%, 7.6%, 7.7%, 7.8%, 7.9%, 8.0%, 8.1%, 8.2%, 8.3%, 8.4%, 8.5% or any value within the range composed of any of the above values.
[0092] The R6T 13 The M1 phase is shown as a gray grain boundary phase in the microstructure cross-section photograph, wherein the atomic percentage of the rare earth element R is 20% to 31%. 13 The M1 phase includes T element, the atomic percentage of T is 60% to 75%, the T element includes Fe and / or Co, and M is selected from one or more of Al, Cu, Ga, Ti, Sn, Zr, and Nb.
[0093] The R-rich phase is shown as a white grain boundary phase in a microstructure cross-section photograph, wherein the atomic percentage of the rare earth element R is 39% to 69%, the R-rich phase includes T elements, the atomic percentage of T is 14% to 61%, and the T elements include Fe and / or Co.
[0094] In some embodiments, the R6T 13 The distribution of the M1 phase satisfies the following conditions: all R6T 13 The percentage of the area of the M1 phase to the total area of the cross section is 5.9% to 8.4%. 13 The percentage of the area of the M1 phase to the total area of the cross-section can be 5.9%, 6.0%, 6.2%, 6.4%, 6.6%, 6.8%, 7.0%, 7.2%, 7.4%, 7.6%, 7.8%, 8.0%, 8.2%, 8.3%, 8.4% or any value within the range formed by any of the above values.
[0095] In some embodiments, the R6T 13 The M1 phase includes Cu element, and the R6T 13 The average atomic percentage of Cu in the M1 phase is 1.5% to 7%. 13 The average atomic percentage of Cu element in the M1 phase is 1.5%, 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, 5.0%, 5.5%, 6.0%, 6.5%, 7.0% or any value within the range composed of any of the above values.
[0096] In some embodiments, the R-rich phase includes Cu element, and the average atomic percentage of Cu element in the R-rich phase is 3.50% to 11.00%, preferably 3.50% to 7.60%. Exemplarily, the average atomic percentage of Cu element in the R-rich phase is 3.5%, 4.0%, 4.5%, 5.0%, 5.5%, 6.0%, 6.5%, 7.0%, 7.5% or any value within the range of any of the above values.
[0097] In some embodiments, the R6T 13 The M1 phase includes Co element, and the R6T 13 The average atomic percentage of Co in the M1 phase is 0.50% to 4%. 13 The average atomic percentage of Co element in the M1 phase is 0.5%, 1.0%, 1.5%, 2.0%, 2.5%, 3.0%, 3.5%, 4.0% or any value within the range consisting of any of the above values.
[0098] In some embodiments, the R-rich phase includes Ga element, and the average atomic percentage of Ga element in the R-rich phase is 0.3-1.5%. For example, the average atomic percentage of Ga element in the R-rich phase is 0.3%, 0.5%, 0.7%, 0.9%, 1.1%, 1.3%, 1.5%, or any value within the range of any of the above values.
[0099] In some embodiments, the NdFeB magnet comprises:
[0100] R: 29.5~32wt%
[0101] B: 0.84~0.92wt%
[0102] Al: 0.3~0.55wt%,
[0103] Ga: 0.3~0.48wt%,
[0104] Co: 0.05-0.6wt%,
[0105] Cu: 0.05-0.3wt%,
[0106] Fe: 66~70wt%.
[0107] In order to reduce the amount of heavy rare earth used, it is necessary to adopt a formula system with lower B content and higher Ga content. In particular, for the preparation of magnets with higher coercivity, when the Cu content in the magnet composition is lower and the Al content is higher, the inventors found that R6T 13 The M1 phase is prone to uneven distribution in the magnet, and some R6T 13The M1 phase is easy to agglomerate in the grain boundary phase of the triangle area. 13 The low proportion of M1 phase is not conducive to the improvement of the coercivity of the magnet. Further research found that the R6T aggregated in the grain boundary phase of the triangle area 13 In the M1 phase, the [Ga] / [M] ratio is larger, the [Al] / [M] ratio is smaller, and [Ga] is R6T 13 The atomic percentage of Ga element in M1 phase, [M] is R6T 13 The atomic percentage of M element in M1 phase, [Al] is R6T 13 The atomic percentage of Al element in M1 phase, that is, Ga element is more likely to be enriched in R6T 13 M1 phase, Al element in R6T 13 The M1 phase is relatively less distributed.
[0108] The present invention effectively optimizes the microstructure of the magnet by rationally controlling the contents of B, Cu, Co, Al, and Ga in the raw material components and combining the three-stage aging process. In particular, after the three-stage aging heat treatment, the R6T 13 The area ratio of the M1 phase also promotes the redistribution of Ga elements, making R6T 13 The [Ga] / [M] ratio in the M1 phase decreases, while the [Al] / [M] ratio increases, which in turn makes the R6T enriched in the grain boundary phase of the magnet triangle region 13 The reduction of the M1 phase enables fine control of the grain boundary structure of the magnet, thereby effectively improving the coercive force of the magnet.
[0109] In some embodiments, the composition of the NdFeB magnet includes R: 29.5-32 wt%. For example, the content of R can be 29.5 wt%, 29.7 wt%, 29.9 wt%, 30.1 wt%, 30.3 wt%, 30.5 wt%, 30.7 wt%, 30.9 wt%, 31.1 wt%, 31.3 wt%, 31.5 wt%, 31.7 wt%, 31.9 wt% or any value within the range of any of the above values.
[0110] In some embodiments, the composition of the NdFeB magnet includes 0.84-0.92 wt % of B. For example, the content of B can be 0.84 wt %, 0.85 wt %, 0.86 wt %, 0.87 wt %, 0.88 wt %, 0.89 wt %, 0.90 wt %, 0.91 wt %, 0.92 wt % or any value within the range of any of the above values.
[0111] In some embodiments, the composition of the NdFeB magnet includes Al: 0.3-0.55 wt%. For example, the content of Al can be 0.30 wt%, 0.32 wt%, 0.35 wt%, 0.38%, 0.40 wt%, 0.42 wt%, 0.45 wt%, 0.48 wt%, 0.50 wt%, 0.52 wt%, 0.55 wt% or any value within the range of any of the above values.
[0112] In some embodiments, the composition of the NdFeB magnet includes Ga: 0.3-0.48 wt %. For example, the content of Ga can be 0.30 wt %, 0.32 wt %, 0.35 wt %, 0.38 wt %, 0.40 wt %, 0.42 wt %, 0.45 wt %, 0.48 wt % or any value within the range of any of the above values.
[0113] In some embodiments, the composition of the NdFeB magnet includes 0.05-0.6 wt % Co. For example, the content of Co can be 0.05 wt %, 0.10 wt %, 0.15 wt %, 0.20 wt %, 0.25 wt %, 0.30 wt %, 0.35 wt %, 0.40 wt %, 0.45 wt %, 0.50 wt %, 0.55 wt %, 0.60 wt % or any value within the range of any of the above values.
[0114] In some embodiments, the composition of the NdFeB magnet includes Cu: 0.05-0.3 wt %. For example, the content of Cu can be 0.05 wt %, 0.08 wt %, 0.10 wt %, 0.12 wt %, 0.15 wt %, 0.18 wt %, 0.20 wt %, 0.22 wt %, 0.25 wt %, 0.28 wt %, 0.30 wt % or any value within the range of any of the above values.
[0115] In some embodiments, the composition of the NdFeB magnet includes Ti and Zr, and the weight ratio of Ti:Zr is 2:1 to 4:1. For example, the weight ratio of Ti:Zr can be 2.0:1, 2.2:1, 2.4:1, 2.6:1, 2.8:1, 3.0:1, 3.2:1, 3.4:1, 3.6:1, 3.8:1, 4.0:1.
[0116] In some embodiments, the composition of the NdFeB magnet includes only one of Ti and Zr, Ti or Zr: 0.15-0.35wt%. Exemplarily, the content of Ti or Zr can be 0.15wt%, 0.17wt%, 0.19wt%, 0.21wt%, 0.23wt%, 0.25wt%, 0.27wt%, 0.29wt%, 0.31wt%, 0.33wt%, 0.35wt% or any value within the range of any of the above values.
[0117] In some embodiments, the total content of the impurity elements is less than 2100 ppm. For example, the total content of the impurity elements is 2100 ppm, 2000 ppm, 1900 ppm, 1800 ppm, 1700 ppm, 1600 ppm, 1500 ppm, 1400 ppm, 1300 ppm, 1200 ppm, 1100 ppm, 1000 ppm or any value within the range of any of the above values.
[0118] In some embodiments, the impurity elements include one or more of C, N and O, the content of O is less than 750 ppm, and the content of N is less than 480 ppm. For example, the content of O can be 750 ppm, 700 ppm, 650 ppm, 600 ppm, 550 ppm, 500 ppm, 450 ppm, 400 ppm, 350 ppm, 300 ppm, or any value within the range of any of the above values. For example, the content of N can be 480 ppm, 450 ppm, 420 ppm, 400 ppm, 380 ppm, 350 ppm, 320 ppm, 300 ppm, 280 ppm, 250 ppm, 220 ppm, 200 ppm, or any value within the range of any of the above values.
[0119] In some embodiments, the R6T 13 The distribution of the M1 phase satisfies the following condition: the area of all R6T13M1 phases in the cross section of the NdFeB magnet accounts for 5.3% to 7.9% of the total area of the cross section. 13 The percentage of the area of the M1 phase to the total area of the cross-section can be 5.3%, 5.5%, 5.7%, 5.9%, 6.1%, 6.3%, 6.5%, 6.7%, 6.9%, 7.1%, 7.3%, 7.5%, 7.7%, 7.8%, 7.9% or any value within the range formed by any of the above values.
[0120] In some embodiments, the R6T 13 The M1 phase contains Ga, and [Ga] represents the R6T13 Ga atomic percentage in the M1 phase, [M] represents the R6T 13 The atomic percentage of the M element in the M1 phase is [Ga] / [M]=0.49-0.61. For example, [Ga] / [M] may be 0.49, 0.51, 0.53, 0.55, 0.57, 0.59, 0.61 or any value within the range of any of the above values.
[0121] In some embodiments, the R6T 13 The M1 phase contains Al, and [Al] represents the R6T 13 Ga atomic percentage in the M1 phase, [M] represents the R6T 13 The atomic percentage of the M element in the M1 phase, [Al] / [M]=0.32-0.45. For example, [Al] / [M] may be 0.32, 0.34, 0.36, 0.38, 0.40, 0.42, 0.44, 0.45 or any value within the range of any of the above values.
[0122] According to the second aspect of the present application, the present application also provides a method for preparing a neodymium iron boron magnet, which comprises:
[0123] 1) using a predetermined raw material alloy to form a quick-setting alloy sheet by a quick-setting process;
[0124] 2) The quick-setting alloy flakes obtained in step 1) are subjected to hydrogen explosion pulverization and jet mill pulverization to obtain alloy powder, wherein the average particle size D50 of the alloy powder is 3 to 5 μm;
[0125] 3) pressing the alloy powder obtained in step 2) under magnetic field orientation, the magnetic field strength is 1.4-2.5T, to obtain a compact, or the alloy powder is pressed under magnetic field orientation and then isostatically pressed to obtain a compact;
[0126] 4) placing the compact obtained in step 3) into a sintering furnace, and performing sintering and aging treatment in a vacuum or inert atmosphere to finally obtain a NdFeB magnet;
[0127] The aging treatment process is a three-level aging process: the temperature of the first level aging is 800-950°C, and the insulation time is 0.5-4h; the temperature of the second level aging is 450-550°C, and the insulation time is 2-10h; the temperature of the third level aging is 600-700°C, and the insulation time is 2-10h.
[0128] The present invention effectively optimizes the microstructure of the magnet by rationally controlling the content of B, Cu, Co, and Al in the raw material components and combining the three-stage aging process. In particular, after the three-stage aging heat treatment, R6T 13The proportion of M1 phase increases, and at the same time, the redistribution of elements such as Cu and Co is promoted, which reduces the Cu content in the R-rich phase. 13 The increase in the content of Cu and Co elements in the M1 phase enables fine control of the grain boundary structure of the magnet, thereby effectively improving the coercive force of the magnet.
[0129] In some embodiments, in step 1), the composition ratio of the raw material alloy of the predetermined configuration refers to the composition of the NdFeB magnet of the first aspect of the present application.
[0130] In some embodiments, in the three-stage aging process, the temperature of the first stage aging is 800-950°C, and the holding time is 0.5-4h. Exemplarily, the temperature of the first stage aging is 800°C, 820°C, 850°C, 880°C, 900°C, 920°C, 950°C, or any value within the range of any of the above values. Exemplarily, the holding time of the first stage aging is 0.5h, 1h, 1.5h, 2h, 2.5h, 3h, 3.5h, 4h, or any value within the range of any of the above values.
[0131] In some embodiments, in the three-stage aging process, the temperature of the second stage aging is 450-550°C, and the holding time is 2-10 hours. Exemplarily, the temperature of the second stage aging is 450°C, 460°C, 470°C, 480°C, 490°C, 500°C, 510°C, 520°C, 530°C, 540°C, 550°C, or any value within the range of any of the above values. Exemplarily, the holding time of the second stage aging is 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, or any value within the range of any of the above values.
[0132] In some embodiments, in the three-stage aging process, the temperature of the third stage aging is 600-700°C, and the holding time is 2-10h. Exemplarily, the temperature of the third stage aging is 600°C, 610°C, 620°C, 630°C, 640°C, 650°C, 660°C, 670°C, 680°C, 690°C, 700°C, or any value within the range of any of the above values. Exemplarily, the holding time of the third stage aging is 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, or any value within the range of any of the above values.
[0133] In some embodiments, in the step 4), the aging treatment process further includes: cooling to 150-250°C after the second stage aging, with a cooling rate of 3-8°C / min; cooling to room temperature after the third stage aging, with a cooling rate of 3-8°C / min. Exemplarily, the cooling rate after the second stage aging can be 3.0°C / min, 3.5°C / min, 4.0°C / min, 4.5°C / min, 5.0°C / min, 5.5°C / min, 6.0°C / min, 6.5°C / min, 7.0°C / min, 7.5°C / min, 8.0°C / min or any value within the range of any of the above values. Illustratively, the cooling rate after the third stage aging can be 3.0°C / min, 3.5°C / min, 4.0°C / min, 4.5°C / min, 5.0°C / min, 5.5°C / min, 6.0°C / min, 6.5°C / min, 7.0°C / min, 7.5°C / min, 8.0°C / min or any value within the range composed of any of the above values.
[0134] In some embodiments, in step 1), the rapid solidification process includes melting the alloy raw material in a vacuum induction melting furnace at a melting temperature of 1400-1500°C, and casting the molten liquid onto a copper roller to obtain a 0.15-0.4 mm rapid solidification alloy sheet. Exemplarily, the melting temperature may be 1400°C, 1410°C, 1420°C, 1430°C, 1440°C, 1450°C, 1460°C, 1470°C, 1480°C, 1490°C, 1500°C, or any value within the range of any of the above values.
[0135] In some embodiments, in the step 4), the process parameters of the sintering include: a sintering temperature of 1030-1120°C, a sintering time of 4-12h, preferably 6-12h. Exemplarily, the sintering temperature is 1030°C, 1040°C, 1050°C, 1060°C, 1070°C, 1080°C, 1090°C, 1100°C, 1110°C, 1120°C or any value within the range of any of the above values. Exemplarily, the sintering time is 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h or any value within the range of any of the above values.
[0136] In some embodiments, in the step 4), the sintering is a two-stage sintering: the sintering temperature of the first stage sintering is 1030-1120°C, and the sintering time is 4-12h; the sintering temperature of the second stage sintering is 10-15°C lower than the sintering temperature of the first stage, and the sintering time of the second stage sintering is 1-3h shorter than the sintering time of the first stage. Exemplarily, the sintering temperature of the first stage sintering is 1030°C, 1040°C, 1050°C, 1060°C, 1070°C, 1080°C, 1090°C, 1100°C, 1110°C, 1120°C, or any value within the range of any of the above values. Exemplarily, the sintering time of the first stage sintering is 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h, or any value within the range of any of the above values.
[0137] In some embodiments, in the step 4), the sintering is a two-stage sintering: the sintering temperature of the second stage sintering is 1015-1110°C, and the sintering time of the second stage sintering is 1-11h. Exemplarily, the sintering temperature of the second stage sintering is 1015°C, 1020°C, 1030°C, 1040°C, 1050°C, 1060°C, 1070°C, 1080°C, 1090°C, 1100°C, 1110°C or any value within the range of any of the above values. Exemplarily, the sintering time of the second stage sintering is 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h or any value within the range of any of the above values.
[0138] In some embodiments, in the step 4), the sintering is a two-stage sintering: a cooling process is also included between the first stage sintering and the second stage sintering, the cooling rate is 4 to 9°C / min, and the heating rate after cooling is 8 to 12°C / min; preferably, the heating rate after cooling is higher than the cooling rate. Exemplarily, the cooling rate between the first stage sintering and the second stage sintering can be 4.0°C / min, 4.5°C / min, 5.0°C / min, 5.5°C / min, 6.0°C / min, 6.5°C / min, 7.0°C / min, 7.5°C / min, 8.0°C / min, 8.5°C / min, 9.0°C / min or any value within the range of any of the above values. Illustratively, the heating rate between the first stage sintering and the second stage sintering can be 8.0°C / min, 8.5°C / min, 9.0°C / min, 9.5°C / min, 10.0°C / min, 10.5°C / min, 11.0°C / min, 11.5°C / min, 12.0°C / min or any value within the range formed by any of the above values.
[0139] In some embodiments, in step 4), the sintering is a two-stage sintering: after the second stage sintering, an inert gas such as argon is introduced to cool to room temperature before a subsequent aging treatment is performed.
[0140] In order to improve the stability, consistency and yield of batch products, the present application regulates the sintering process and adopts a two-stage sintering method. The second-stage sintering temperature is 10-15°C lower than the first-stage sintering temperature, and the second-stage sintering time is 1-3h shorter than the first-stage sintering time. A cooling process is included between the first-stage sintering and the second-stage sintering, and the heating rate is preferably higher than the cooling rate. Through the adjustment of the above-mentioned sintering process, the grains can achieve consistent growth, the grains are refined, the main phase is ensured to be uniform and defect-free, and the foundation is laid for the fine regulation of the grain boundary phase in the subsequent aging process.
[0141] The inventors found that if the present application adopts the secondary aging process of the prior art, the reaction of the grain boundary phase is not easy to control, and the Ga element is easy to aggregate during the process. 13 The M1 phase is unevenly distributed, resulting in a larger R6T 13 M1 phase, the overall squareness of the magnet deteriorates and the coercivity is low. When low-temperature secondary aging is performed, the liquid phase can be further promoted to flow fully, so that the low-melting point elements and rare earth elements are evenly distributed. When the third aging is performed, part of the main phase can participate in the reaction. The Al element inside the main phase participating in the reaction can partially replace the Ga element in the liquid phase, and cooperate with the Ga element in the original grain boundary phase to reconfigure the composition; during the liquid phase solidification process, the Ga element and the Al element enter the R6T 13 The M1 phase promotes the role of Ga in the formation of grain boundary phases, generating a smaller area of uniformly distributed R6T 13 M1 phase, thereby increasing R6T 13 The M1 phase ratio improves the demagnetizing coupling effect and realizes the fine structure control of the magnet grain boundary, which is beneficial to the improvement of coercive force and squareness. The specific performance includes that the element characteristics in the magnet grain boundary phase are that the [Ga] / [M] ratio is reduced and the [Al] / [M] ratio is increased.
[0142] The test methods used in this application are as follows:
[0143] Microstructure test method:
[0144] After the magnet is sampled, any 10 or more cross sections of the magnet perpendicular to the orientation direction are tested by scanning electron microscope, and the analysis of all triangular grain boundary phases in each microstructure cross section is statistically analyzed, and the percentage of the area of all triangular grain boundary phases in each cross section to the total area of the cross section is calculated, and then the average value of all cross sections is calculated as the percentage of the area of all triangular grain boundary phases in the cross section of the NdFeB magnet to the total area of the cross section; the size of the observation area is, for example, 40μm×40μm and 75μm×75μm; the magnification is 2000 to 5000 times. Image-proplus image analysis software is used for statistical analysis, and the image contrast is distinguished. 13 The M1 phase is shown as a gray grain boundary phase, and the R-rich phase is shown as a white grain boundary phase. It can be obtained that all R6T 13 The percentage of the area of the M1 phase to the total area of the cross section. Figure 1-4 As shown, the grain boundary phase in the triangle area marked by ○ is R6T 13 M1 phase, the grain boundary phase in the triangle area marked by △ is the R-rich phase. EDS energy spectrum analysis is used to test the R6T in NdFeB magnets 13 The atomic percentage of each element in the M1 phase and the R-rich phase is obtained, and the element data of at least 20 points are obtained. The [Ga] / [M] ratio and [Al] / [M] value of each point are calculated, and the average value is calculated to obtain the data.
[0145] The magnetic properties of the magnets were measured by a BH curve measuring instrument (NIM-200). Specific embodiments
[0147] Example 1-1
[0148] Magnet formula:
[0149]
[0150] 1) The alloy raw materials prepared according to the above formula are cast into raw material alloy quick-setting sheets by using a quick-setting process: the alloy raw materials are melted in a vacuum induction melting furnace at a melting temperature of 1500° C., and the molten liquid is cast onto a copper roller to obtain a 0.25 mm quick-setting alloy sheet.
[0151] 2) The raw alloy quick-solidification sheets are hydrogen crushed and finely pulverized to obtain raw alloy powder; wherein the hydrogen absorption pressure of the hydrogen crushing is 0.3 MPa, the dehydrogenation temperature is 560°C, the fine pulverization is carried out in an air flow mill, the grinding pressure of the air flow mill is 0.68 MPa, and the average particle size D50 of the raw alloy powder is 4 μm.
[0152] 3) The raw alloy powder is subjected to a molding process: the alloy powder obtained in step 2) is pressed and molded under magnetic field orientation with a magnetic field strength of 1.5 T to obtain a compact.
[0153] 4) placing the compact obtained in step 3) into a sintering furnace, and performing sintering and aging treatment in a vacuum or inert atmosphere to finally obtain a NdFeB magnet.
[0154] The parameters of the sintering process are: sintering temperature is 1060° C., and sintering time is 8 hours.
[0155] The aging process adopts a three-stage aging process: the first stage aging treatment is carried out for 2 hours after heating to 900°C at 7°C / min, the second stage aging treatment is carried out for 6 hours after cooling to 200°C, the second stage aging treatment is carried out for 6 hours after heating to 500°C at 5°C / min, the third stage aging treatment is carried out for 6 hours after cooling to 200°C, the third stage aging treatment is carried out for 6 hours after heating to 630°C at 5°C / min, and the final magnet is obtained by cooling to room temperature.
[0156] Example 1-2
[0157] Magnet formula:
[0158]
[0159]
[0160] The specific preparation steps of Example 1-2 are exactly the same as those of Example 1-1.
[0161] Examples 1-3
[0162] Magnet formula:
[0163]
[0164] The specific preparation steps of Example 1-3 are exactly the same as those of Example 1-1.
[0165] Comparative Example 1-1
[0166] The same magnet formula as in Example 1-1 was used, and the preparation steps except for the aging treatment were the same as in Example 1.
[0167] The only difference is that the aging treatment process adopts a conventional two-stage aging process: the aging treatment includes a first-stage aging treatment and a second-stage aging treatment, the temperature of the first-stage aging treatment is 890°C, and the holding time is 4 hours; the temperature of the second-stage aging treatment is 500°C, and the holding time is 8 hours, to obtain a NdFeB magnet.
[0168] Comparative Example 1-2
[0169] A different magnet formula from that of Example 1-1 was used, and the preparation steps were the same as those of Example 1.
[0170] Magnet formula:
[0171]
[0172] The magnetic properties test data of Examples 1-1 to 1-3 and Comparative Examples 1-1 to 1-2 are as follows:
[0173]
[0174]
[0175] The microstructure test results of Example 1-1 and Comparative Example 1-1 are as follows:
[0176] 1) The percentage of the area of all triangular grain boundary phases in the cross section of the NdFeB magnet in Example 1-1 to the total area of the cross section is 7.29%; the triangular grain boundary phases in Example 1-1 include R6T 13 M1 phase and R-rich phase, all R6T in the cross section of the NdFeB magnet described in Example 1-1 13 The percentage of the area of the M1 phase to the total area of the cross section is 6.29%.
[0177] The percentage of the area of all triangular grain boundary phases in the cross section of the NdFeB magnet in Comparative Example 1-1 to the total area of the cross section is 5.03%. 13 The percentage of the area of the M1 phase to the total area of the cross section is 4.03%.
[0178] 2) The R-rich phase (white grain boundary phase) of Example 1-1 includes Cu element, and the average atomic percentage of Cu element is 5.26%; R6T of Example 1-1 13 The M1 phase (gray grain boundary phase) includes the Cu element, and the average atomic percentage of the Cu element is 4.01%.
[0179] The R-rich phase (white grain boundary phase) of Comparative Example 1-1 includes Cu element, and the average atomic percentage of Cu element is 14.37%. 13 The M1 phase (gray grain boundary phase) includes Cu element, and the average atomic percentage of Cu element is 0.65%.
[0180] 3) R6T of Example 1-1 13 The M1 phase includes Co element, wherein the average atomic percentage of the Co element is 1.62%.
[0181] R6T of Comparative Example 1-1 13 The M1 phase includes Co element, wherein the average atomic percentage of the Co element is 0.24%.
[0182] 4) The R-rich phase of Example 1-1 includes Ga element, wherein the average atomic percentage of Ga element is 0.56%.
[0183] The R-rich phase of Comparative Example 1-1 included Ga element, wherein the average atomic percentage of Ga element was 1.39%.
[0184] As described above, Comparative Example 1-1 uses the same magnet formula as Example 1-1, but uses a conventional secondary aging process; the triangular region grain boundary phase area ratio and R6T 13 The M1 phase area ratio is significantly lower than that of Example 1-1. 13 The M1 phase (gray grain boundary phase) has significantly higher Cu and Co elements, and the R-rich phase of Example 1-1 has relatively lower Ga elements. From the magnetic performance data, compared with the examples, Comparative Example 1-1 has significantly lower coercivity of 13.78 kOe and squareness of 98.3%.
[0185] Comparative Example 1-2 uses a different magnet formula from Example 1-1, but the preparation steps are the same as Example 1-1. From the magnetic performance data, compared with the examples, Comparative Example 1-2 has significantly lower remanence of 13.81 kGs and squareness of 97.6%.
[0186] Example 2-1
[0187] Magnet formula:
[0188]
[0189] 1) The alloy raw materials prepared according to the above formula are cast into raw material alloy quick-setting sheets by using a quick-setting process: the alloy raw materials are melted in a vacuum induction melting furnace at a melting temperature of 1450° C., and the molten liquid is cast onto a copper roller to obtain a 0.25 mm quick-setting alloy sheet.
[0190] 2) The raw alloy quick-solidification sheets are hydrogen crushed and finely pulverized to obtain raw alloy powder; wherein the hydrogen absorption pressure of the hydrogen crushing is 0.3 MPa, the dehydrogenation temperature is 560°C, the fine pulverization is carried out in an air flow mill, the grinding pressure of the air flow mill is 0.68 MPa, and the average particle size D50 of the raw alloy powder is 4 μm.
[0191] 3) Forming the raw alloy powder: The alloy powder obtained in step 2) is pressed and formed under magnetic field orientation with a magnetic field strength of 1.4 T to obtain a compact.
[0192] 4) placing the compact obtained in step 3) into a sintering furnace, and performing sintering and aging treatment in a vacuum or inert atmosphere to finally obtain a NdFeB magnet.
[0193] The sintering process adopts two-stage sintering. After sintering at a temperature of 1070°C for 6 hours, argon gas is passed to cool to 450°C, and then the temperature is increased to 1060°C at 10°C / min for secondary sintering for 5 hours. After that, argon gas is passed to cool to room temperature to obtain a sintered blank.
[0194] The aging process adopts a three-stage aging process: the first stage aging treatment is carried out for 2 hours after heating to 900°C at 7°C / min, the second stage aging treatment is carried out for 6 hours after cooling to 200°C, the second stage aging treatment is carried out for 6 hours after heating to 500°C at 5°C / min, the third stage aging treatment is carried out for 6 hours after cooling to 200°C, the third stage aging treatment is carried out for 6 hours after heating to 630°C at 5°C / min, and the final magnet is obtained by cooling to room temperature.
[0195] Example 2-2
[0196] Magnet formula:
[0197]
[0198] The specific preparation steps of Example 2-2 are exactly the same as those of Example 2-1.
[0199] Example 2-3
[0200] Magnet formula:
[0201]
[0202] The specific preparation steps of Example 2-3 are exactly the same as those of Example 2-1.
[0203] Comparative Example 2-1
[0204] The same magnet formula as in Example 2-1 was used, and the preparation steps except for the sintering process and aging treatment were the same as in Example 2.
[0205] The only difference is that the sintering process and aging treatment use conventional sintering process and secondary aging process respectively. The conventional sintering process is sintering at a temperature of 1050℃ for 10h. The aging treatment includes the first aging treatment and the second aging treatment. The temperature of the first aging treatment is 890℃ and the holding time is 4h; the temperature of the second aging treatment is 500℃ and the holding time is 8h, and the NdFeB magnet is obtained.
[0206] Comparative Example 2-2
[0207] A different magnet formula from that of Example 1-1 was used, and the preparation steps were the same as those of Example 1.
[0208] Magnet formula:
[0209]
[0210] The magnetic properties test data are as follows:
[0211]
[0212] The microstructure test results of Example 2-1 and Comparative Example 2-1 are as follows:
[0213] 1) The triangular grain boundary phase of Example 2-1 includes R6T 13 M1 phase, all R6T in the cross section of the NdFeB magnet described in Example 2-1 13 The area of the M1 phase accounts for 7.40% of the total area of the cross section.
[0214] The triangular grain boundary phase of Comparative Example 2-1 includes R6T 13 M1 phase, all R6T in the cross section of the NdFeB magnet described in Comparative Example 2-1 13 The area of the M1 phase accounts for 5.20% of the total area of the cross section.
[0215] 2) R6T of Example 2-1 13 The M1 phase includes Ga and Al, and the atomic ratio of [Ga] / [M] is 0.51, and the atomic ratio of [Al] / [M] is 0.41.
[0216] R6T of Comparative Example 2-1 13 The M1 phase includes Ga and Al, and the atomic ratio of [Ga] / [M] is 0.65, and the atomic ratio of [Al] / [M] is 0.30.
[0217] As described above, Comparative Example 2-1 uses the same magnet formula as Example 2-1, but uses a conventional sintering process and a secondary aging process; the NdFeB magnets obtained in Comparative Example 2-1 have R6T 13 The M1 phase area ratio of 5.20% is significantly lower than the corresponding data of Example 1-1 (7.40%); compared with Comparative Example 2-1, the R6T of Example 2-1 is 13 The M1 phase has a relatively high [Al] / M and a relatively low [Ga] / [M]. From the magnetic property data, compared with the embodiments, the comparative example 2-1 has a relatively low coercive force of 17.31 kOe and a significantly low squareness of 98.2%.
[0218] Comparative Example 2-2 uses a different magnet formula from Example 2-1, but the preparation steps are the same as Example 2-1. From the magnetic performance data, compared with the examples, Comparative Example 2-2 has significantly lower coercivity of 16.15 kOe and squareness of 97.5%.
[0219] Although multiple embodiments of the present application have been shown and described herein, it is obvious to those skilled in the art that such embodiments are provided only by way of example. Those skilled in the art can think of many changes, modifications and alternatives without departing from the thought and spirit of the present application. It should be understood that in the process of practicing the present application, various alternatives to the embodiments of the present application described herein can be adopted. The attached claims are intended to limit the scope of protection of the present application, and therefore cover equivalents or alternatives within the scope of these claims.
Claims
1. A neodymium iron boron magnet, comprising main phase grains, thin layer grain boundary phases and triangular region grain boundary phases, characterized in that: The NdFeB magnet comprises: R: 28~33wt% B: 0.84~0.94wt%, Co: 0.05~1wt%, Cu: 0.05~0.55wt%, Ga: 0.3~0.6wt%, M2: 0-0.55wt%, wherein M2 is selected from one or both of Al and Sn, M3: 0.1-0.6wt%, wherein M3 is selected from one or two of Zr and Ti, Fe: 66-70wt%; Wherein, R is a rare earth element, and R includes at least PrNd; The triangular region grain boundary phase includes R6T 13 M1 phase, the R6T 13 The M1 phase includes M elements and T elements, wherein the M elements are selected from any two or more elements of Al, Cu, Ga, Ti, Sn and / or Zr, and the T elements include Fe and / or Co. The R6T 13 The percentage of the sum of the areas of the M1 phase to the cross-sectional area of the microstructure is 5.2% to 8.4%.
2. The NdFeB magnet according to claim 1, characterized in that: The NdFeB magnet comprises: R: 28~31wt% B: 0.84~0.92wt% Co: 0.05-0.6wt%, Cu: 0.3~0.55wt%, Al: 0~0.35wt%, Ga: 0.3~0.48wt%, M3: 0.15~0.3wt% Fe: 66~70wt%.
3. The NdFeB magnet according to claim 2, characterized in that: The distribution of the triangular region grain boundary phase meets the following conditions: the percentage of the area of all triangular region grain boundary phases in the microstructure cross section of the NdFeB magnet to the total cross section area is 6.5% to 8.5%; and the triangular region grain boundary phase includes R6T 13 M1 phase and R-rich phase, the R6T 13 The distribution of the M1 phase satisfies the following conditions: all R6T 13 The percentage of the area of the M1 phase to the total area of the cross section is 5.9% to 8.4%.
4. The NdFeB magnet according to claim 2, characterized in that: The R6T 13 The M1 phase includes Cu element, and the R6T 13 The average atomic percentage of Cu element in the M1 phase is 1.5% to 7%.
5. The NdFeB magnet according to claim 3, characterized in that: The R-rich phase includes Cu element, and the average atomic percentage of Cu element in the R-rich phase is 3.50% to 11.00%, preferably 3.50% to 7.60%.
6. The NdFeB magnet according to claim 3, characterized in that: The R6T 13 The M1 phase includes Co element, and the R6T 13 The average atomic percentage of Co element in the M1 phase is 0.50% to 4%.
7. The NdFeB magnet according to claim 3, characterized in that: The R-rich phase includes Ga element, and the average atomic percentage of Ga element in the R-rich phase is 0.3-1.5%.
8. The NdFeB magnet according to claim 1, characterized in that: The NdFeB magnet comprises: R: 29.5~32wt% B: 0.84~0.92wt% Al: 0.3~0.55wt%, Ga: 0.3~0.48wt%, Co: 0.05-0.6wt%, Cu: 0.05~0.3wt% Fe: 66~70wt%.
9. The NdFeB magnet according to claim 8, characterized in that: The R6T 13 The distribution of the M1 phase satisfies the following conditions: all R6T 13 The percentage of the area of the M1 phase to the total area of the cross section is 5.3% to 7.9%.
10. The NdFeB magnet according to claim 9, characterized in that: The R6T 13 The M1 phase contains Ga, and [Ga] represents the R6T 13 Ga atomic percentage in the M1 phase, [M] represents the R6T 13 The atomic percentage of the M element in the M1 phase is [Ga] / [M] = 0.49 to 0.61; The R6T 13 The M1 phase contains Al, and [Al] represents the R6T 13 The atomic percentage of Al in the M1 phase, [M] represents the R6T 13 The atomic percentage of M element in the M1 phase is [Al] / [M]=0.32~0.
45.
11. The NdFeB magnet according to any one of claims 1 to 10, characterized in that: R does not include heavy rare earth elements.
12. A method for preparing a neodymium iron boron magnet, characterized in that: include: 1) using a quick-setting process to prepare quick-setting alloy sheets using alloy raw materials of a predetermined configuration; 2) The quick-setting alloy flakes obtained in step 1) are subjected to hydrogen explosion pulverization and jet mill pulverization to obtain alloy powder, wherein the average particle size D50 of the alloy powder is 3 to 5 μm; 3) pressing the alloy powder obtained in step 2) under magnetic field orientation, the magnetic field strength is 1.4-2.5T, to obtain a compact, or the alloy powder is pressed under magnetic field orientation and then isostatically pressed to obtain a compact; 4) placing the compact obtained in step 3) into a sintering furnace, and performing sintering and aging treatment in a vacuum or inert atmosphere to finally obtain a NdFeB magnet; The aging treatment process is a three-level aging process: the temperature of the first level aging is 800-950°C, and the insulation time is 0.5-4h; the temperature of the second level aging is 450-550°C, and the insulation time is 2-10h; the temperature of the third level aging is 600-700°C, and the insulation time is 2-10h.
13. The preparation method according to claim 12, characterized in that: In the step 4), the aging treatment process further comprises: cooling to 150-250°C after the second aging, with a cooling rate of 3-8°C / min; cooling to room temperature after the third aging, with a cooling rate of 3-8°C / min.
Citation Information
Patent Citations
Neodymium iron boron sintering magnet without heavy rare earth and preparation method thereof
CN108878090A
R-T-B series permanent magnet material as well as preparation method and application thereof
CN111326306A
Neodymium-iron-boron magnet and preparation method thereof
CN119170367A
Ndfeb magnet material, preparation method and application thereof
TW202342783A
R-t-b based sintered magnet and motor
US20160180993A1
Cited By
Neodymium-iron-boron magnet and preparation method thereof
CN120636993A
Neodymium-iron-boron magnet and method for producing the same
CN120636993B
Sintered neodymium-iron-boron magnet and preparation method thereof
CN120824090A
Neodymium-iron-boron magnet for ultra-high-speed motor and preparation method and application thereof
CN120977712A
High-performance heavy-rare-earth-free magnet and preparation method thereof
CN121416253A